2016
DOI: 10.4236/aim.2016.68056
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Profile of <i>Oreochromis niloticus</i> Harvested from E-Waste Polluted Vials and Associated Fungi

Abstract: This study was designed to investigate the possible variation in bioaccumulation of heavy metals (lead, cadmium, zinc, cobalt, chromium, nickel, and manganese) in the tissue of harvested Oreochromis niloticus (tilapia) and the associated fungi from vials treated with soil from e-waste dumpsite and soil without e-waste. E-waste is electronic waste which contains valuable metals as well as potential environmental contaminants. The heavy metals in soil and fish samples were determined using flame atomic absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was observe the bioaccumulation of Pb, Cd, Mn, Co, Ni, and other. The author concluded that e-waste can contaminate the soil in recycle area, wich represent a contamination risk to fishes in water near e-waste (Sanusi, 2016). In other Nigerian study study was investigated the possible contamination of water and soil samples from alaba, an International Electronics Market (AIEM) situated in Lagos.…”
Section: E-waste Contaminationmentioning
confidence: 99%
“…It was observe the bioaccumulation of Pb, Cd, Mn, Co, Ni, and other. The author concluded that e-waste can contaminate the soil in recycle area, wich represent a contamination risk to fishes in water near e-waste (Sanusi, 2016). In other Nigerian study study was investigated the possible contamination of water and soil samples from alaba, an International Electronics Market (AIEM) situated in Lagos.…”
Section: E-waste Contaminationmentioning
confidence: 99%